TRADISI LARANGAN PERKAWINAN KEBO MBALIK KANDANG PERSPEKTIF ‘URF (Studi Kasus Desa Sidorejo Kecamatan Ponggok Kabupaten Blitar) - Afif, Abdullah; Rohim, Mif; Zulfa, Nadiya (Irtifaq, 2020)
Abstract: This article discusses the tradition of the prohibition of marriage in Kebo Mbalik Kandang in Sidorejo, Ponggok District, Blitar Regency in the Perspective ‘Urf. By using a qualitative descriptive approach in the form of case studies, researchers collect data by observation, interview, and documentation techniques and analyze the results with data reduction procedures, data presentation, and drawing conclusions. The results of the study showed that the first backbiting marriage was a marriage that was conducted if someone was born in an area, so that person could not be married to someone from that area as well. Second, the implementation of the tradition of backbirth of the cage in the village of Sidorejo, for some people still holding and applying the tradition within the scope of the family, citing anxiety about the impact caused. And there are some people who already do not trust the tradition of back cage because of the development of an increasingly modern era, and the mindset of a society that continues to grow with the information that is widely circulating on social media. ‘Urf is the habit of the majority of people, both in words and deeds. In terms of assessing the good and bad or f urf of the traditional tradition of Kebo Mbalik Kandang marriage in Sidorejo village, Ponggok District, Blitar Regency is divided into two, namely urf shahih dan ‘urf fasid. Keywords: Prohibition of Marriage, Tradition Kebo Mbalik Kandang, Perspective of ‘Urf